Pesticide and antibiotic residues in freshwater aquaculture fish : chemical risk assessment from farm to table - Abu Bakar, Ibrahim; Ayub, Mohd Khan; Muhd Yatim, Ayob; Abdullah Sani, Norrakiah (2010)
The qualitative chemical risk assessments of freshwater aquaculture fish from farms, markets and food premises have been carried out in six main production districts in Malaysia. Three species of fish were involved in this study [red tilapia (Oreachromis sp. red hybrids), keli (Clarias spp.) and patin (Pangasius sutchii)]. About 240 fresh fish (90 red tilapia, 60 keli and 90 patin) were randomly collected direct from their farms (earth ponds, floating net cages and exmining pools). Another 240 fish with the same ratios as farm fish samples were also randomly collected from various markets (wet markets, local markets called ‘pasar tani’ and night markets). The same number of samples with the same ratio of ready-to-eat fish from food premises (restaurants, food stalls and night market food stalls) were also collected. The fish were analyzed for chemical hazards, including pesticide residues and antibiotic residues. All data were then statistically analyzed. The results revealed that there were low chemical hazards in fresh water aquaculture fish. Pesticide and antibiotic residues were only detected in 2.9% and 5.8% of farm fish samples respectively.